PENGARUH TINGKAT SUKU BUNGA BANK INDONESIA DAN NILAI TUKAR RUPIAH TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN BATUBARA YANG TERCATAT DI BURSA EFEK INDONESIA - Fionita, Ita (Jurnal Manajemen dan Keuangan, 2011)
The problem of this research is how big the influence of rate of interest of Indonesian bank and Rupiah exchange rate toward stock market price of Coal Mining Company at Indonesian Bursary Effect in the pre and for 2 (two) months of global crisis. The purpose of this research is to measure the influence between the rate of interest of Indonesian bank and Rupiah exchange rate toward stock market price of Coal Mining Company at the recording of Indonesian Bursary Effect during pre- and post-two months of global crisis, that is during the period of July to November 2008.The method of research here used both of primary and secondary data and data collecting technique through library research and field research, that is through observation and documentation. The data is analyzed by multiple linier regression.Based on the result of data analysis and hypothesis testing is how big the influence of rate of interest of Indonesian Bank (X1) and Rupiah Exchange Rate (X2) during two months before global crisis toward Stock Market Price (Y) could be revealed from the high of multiple determination coefficient value (R2), that is 0,712 or statistically 71,20% of Stock Market Price is influenced by the rate of interest of Indonesian bank and Rupiah Exchange Rate. The rest (100% - 71,20%) = 28,80% of Stock Market Price is influenced by other factors besides those two independent variables. It is also supported from statistical accounting that shows Freckoner > Ftabel or 49,536 > 3,23. For the two months during global crisis, the high of multiple determination coefficient value (R2) is 0,7000 or statistically 70,00% of Stock Market Price is influenced by the rate of interest of Indonesian Bank and Rupiah Exchange Rate.Key words: Rate of Interest of Indonesian Bank, Rupiah Exchange Rate, Stock Market Price.